Mass Balance Status of Indian Himalayan Glaciers: A Brief Review - Singh, Shruti; Kumar, Rajesh; Dimri, A. P. (Frontiers in Environmental Science, 2018)
Glacier mass balance is the direct and undelayed response to climate change and hence it is one of the essential variables required for climate system monitoring. This paper presents a brief review of the glacier mass balance status and their analysis under the changing climate in the Indian Himalayan Region (IHR). The reported results of mass balance in the region give the view of continuous negative mass balance with few exceptions for a year or two reflecting the overall negative mass balance with increasing trend in recent decades. This has coordination with continuous increasing pattern of temperature and decreasing (few not significant) pattern of precipitation. The continuous negative mass balance and rising temperature in the region clearly indicate the impact of warming in reducing the storage of snow and ice in the region with the future implication of shortage of fresh water availability in the snow-glacier fed river system. This will have further implication to the downstream communities for their livelihood.